Profile of Patients with Maxillofacial Space Infections and Associated Risk Factors - Srikanth Gadicherla; Kirti Manglani; Kalyana C. Pentapati; Adarsh Kudva; Chithra Aramanadka; Rajaji Chandravel (The Scientific World Journal)
Objective. To evaluate the profile of patients operated for maxillofacial space infections and associated risk factors for the length of hospital stay. Materials and Methods. We conducted a retrospective study among patients operated for maxillofacial infections at our center from 2010 to 2020. Information collected from the records were age, sex, type and number of spaces involved, clinical signs and symptoms (pain, swelling, toothache, sore throat, otalgia, hoarseness, headache, cough, neck swelling, rancid breath, sialorrhea, gingival swelling, muffled voice, trismus, fever, dysphagia, odynophagia, malaise, lymphadenopathy, dyspnoea, pus discharge), treatment modality, total leukocyte count, evidence of bacterial growth, comorbidities, complications if any and length of hospital stay. Results. A total of 128 medical records were examined, out of which 59 were female. The mean age was 38.59 ± 19.7 and the length of hospital stay was 7.56 ± 3.8 days. The most commonly involved space was submandibular space (46.1%) and the common symptoms reported were swelling (99.2%), pain (86.7%), and trismus (68%). Four patients had complications like necrotizing fasciitis (1.6%), pneumonia (0.8%), and death in one patient (0.8%). Logistic regression showed that patients more than 36 years of age, male sex, evidence of bacterial growth, and diabetics had higher odds of increased hospital stay (>6 days). Multiple logistic regression analysis showed that age (P=0.015; OR: 2.98) and evidence of bacterial culture (P=0.001; OR:6.64) were potential predictors associated with increased hospital stay. Conclusion. Our study showed that the age of the patient and evidence of bacterial culture were potential predictors of prolonged hospital stay among patients operated for maxillofacial space infections.